Scientific Potential of Fish Species Used as Medicine by Indigenous and Non-Indigenous Groups of North East India: A Review with Supporting Research-Based Studies - Sonar, Tinnu; Gogoi, Preronaa; Shah, Bibha; Prasad, Neha Kumari (Asian Journal of Biological and Life Sciences, 2025)
Background: Northeast India is rich in biodiversity, sustaining abundant aquatic fauna. The Indigenous and non-indigenous groups rely on their surrounding biosphere for food and medicines; they use numerous ichthyofauna in their environment to treat diseases. This review aims to compare the use of fish species in therapeutic practices by Indigenous and non-indigenous groups of Northeast India, and assess their scientific potential through available literature, moreover the review, highlights the fish resource management practices by these groups. Materials and Methods: Accessible literature from authentic sources like Scopus, Web of Science and Google Scholar etc., has been used to write this review. 53 articles were initially collected, but 38 articles were included based on pertinence to our study. Conclusion: This review recorded around 48 fish species with medicinal properties utilised by different communities in the states to cure diseases like anaemia, wounds, respiratory issues, and so forth. Out of 24 families, the Cyprinidae family appears to be highly utilised by numerous groups. The Bodo’s of Assam leads in f ish therapy, with approximately 41%, whereas tribes of Tripura utilise ichthyotherapy to a lesser extent compared to other groups of North East India. This study disclosed notable therapeutic compounds reported from fish, like docosahexaenoic acid, eicosapentaenoic acid and anticancer peptides. Furthermore, indigenous practices of conservation and sustainable utilization of fish resources have also been documented. More on-site research and documentation, scientific experiments to validate the medicinal properties of fish, their risk assessment, and effective conservation measures are the pressing need.
Keywords: Cyprinidae; Ichthyofauna; Northeast India; Therapeutic compounds